Dedramatising ideology: style, interpellation and impersonality in Denise Riley. Issue 4 (3rd April 2022) - Hartley, Daniel
ABSTRACT: This article explores the interrelationship of style, interpellation and impersonality in the writings of Denise Riley. Part one performs a detailed reading of Riley's essay 'Malediction', focussing on her theory of interpellation and her visceral sense of the materiality of language. It articulates the philosophical stakes of the essay by taking seriously its sustained, playful engagement with Hegel's Phenomenology of Spirit, and by emphasising the intrinsically Spinozist and dramaturgical elements of Althusser's theory of interpellation. It also seeks to elucidate the philosophical and political import of Riley's own critical style, which combines Stoicism (an 'ethics' in the broad sense), a materialist philosophy of language, and a distinctive poetics. The second part explores Riley's theory of style and literary composition. It engages with Riley's notions of ventriloquy and autoventriloquy, suggesting that her approach to style tends to stress the writer's guilty susceptibility to words. The final part considers Riley's elegy 'A Part Song' and the fraught manner in which grief accentuates contradictions endemic to style and authenticity alike. It argues that Riley harnesses the tensions of echo and interpellation to produce a poem that functions as much on the level of semi-conscious poetic association as via the interpellative mode of apostrophe.